Developing Arabic Grammar Materials Based on Contextual Learning at Islamic Boarding School in Indonesia - Hamidah Hamidah; Yulia Rahmah; Uswatun Hasanah; Selvianor Selvianor; Ajahari Ajahari (Universitas Islam Negeri Palangka Raya, 2024)
This study aims to describe the development of contextual-based supplementary Nahwu teaching materials in five pesantren in Central Kalimantan using the Matan al-Ajrumiyyah text. The research uses a descriptive qualitative and quantitative EDDIE model approach. The subjects are seven ustadz. Data were collected through observation, interviews, documentation, and questionnaires. Experts validated the teaching materials. Qualitative data were analyzed using Miles and Huberman's method, involving data reduction, display, and conclusion drawing. Quantitative data from questionnaires were analyzed using the mean formula. The analysis revealed a need to shift from traditional to contextual-based learning, leading to the development of supplementary Nahwu teaching materials. The design phase identified the learning experiences and specific skills needed by the students. The designed materials included introductions (apperception), examples, explanations, exercises, conclusions, and reflections. The development phase involved creating supplementary materials to achieve the learning objectives, along with determining strategies, methods, and media. Expert validation showed an average validity score of 3.71, with a validity rate of 92.75%, categorizing it as very valid and usable without revision. Theoretical implications suggest that contextual-based Nahwu learning helps learners understand Nahwu and apply Arabic communication. Educational institutions teaching Nahwu can implement contextual-based learning to facilitate students' application of Nahwu.